Creating A Standardized Test For The Vocational High School English Final Examination: An Alternative - Ashadi, Ashadi (English Education Department, Universitas Islam Indonesia, 2008)
The final examination has a significant impact on all stakeholders in corresponding education. It has become a general measurement of success among them and the results reflect the students' and teachers' performance. The ministry of education has selected TOEIC as the vocational high school English final examination in response to the implementation of the Competency-Based Curriculum since 2004. The last two trials of the examinations created a lot of controversies both in the number of failures and their implications to scoring system.This article conveys reasonable objections to the adoption of international wide scale testing to the English education in Indonesia. Several issues will be addressed to the concern which leads to these failures including the decision to apply TOEIC to measure students' language competencies, the ethical issues in language testing, validity and reliability. These all lead to further idea of the construction of a good standardized English test as high school English final examination.